2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2011
DOI: 10.1109/icassp.2011.5946613
|View full text |Cite
|
Sign up to set email alerts
|

Temporal hysteresis model of time varying subjective video quality

Abstract: Video quality assessment (QA) continues to be an important area of research due to the overwhelming number of applications where videos are delivered to humans. In particular, the problem of temporal pooling of quality sores has received relatively little attention. We observe a hysteresis effect in the subjective judgment of timevarying video quality based on measured behavior in a subjective study. Based on our analysis of the subjective data, we propose a hysteresis temporal pooling strategy for QA algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 8 publications
2
109
0
Order By: Relevance
“…The analysis below is simplistic, but much work remains on developing good behavioral models of temporal quality judgements of dynamically changing video distortions. Our first attempt at understanding this new problem is detailed in [32].…”
Section: F Evaluation Of Temporal Quality Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis below is simplistic, but much work remains on developing good behavioral models of temporal quality judgements of dynamically changing video distortions. Our first attempt at understanding this new problem is detailed in [32].…”
Section: F Evaluation Of Temporal Quality Scoresmentioning
confidence: 99%
“…Thus a total of 450 temporal scores were collected for each 15 second video. The temporal scores so obtained were then processed as in [32], in order to produce a temporal MOS (z-score) for each video. Specifically, let be the score assigned to the video by subject in session , where each video is of length .…”
Section: F Evaluation Of Temporal Quality Scoresmentioning
confidence: 99%
“…Throughput variations in the network lead to higher video quality variations which are regarded as leading to lower end user QoE [5][6] [7]. This was reconfirmed in [8] where it was shown that the average quality of the complete video session is often not the correct metric of user's QoE due to hysteresis effect in which the current QoE of a user is negatively influenced by drastic changes in video quality in the recent past.…”
mentioning
confidence: 73%
“…An objective full reference quality metric multi-scale structural similarity index (MS-SSIM) [15] is used for the frame level quality assessment of the decoded distorted video stream. In order to predict the overall objective quality score, the frame-level quality scores are temporally pooled accounting for the fact that users respond strongly to drops in video quality [8]. Unlike temporal averaging, this pooling strategy takes into account the effect of bad quality experienced in the recent past into the objective estimate of quality at the current instant.…”
Section: A Real-time Video Usersmentioning
confidence: 99%
See 1 more Smart Citation